2008
DOI: 10.1007/s00436-008-1139-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of human and bovine Cryptosporidium isolates in Thailand

Abstract: This study was performed to determine the prevalence and genotypes of Cryptosporidium species among HIV patients and cattle in Thailand. Stool specimens were collected from 46 HIV patients from Prabat Nampu Temple, Lop Buri Province in central Thailand. Two hundred fecal samples from dairy cattle were collected from seven farms in Chon Buri Province, the eastern part of Thailand. Each sample was concentrated by Sheather's sucrose flotation technique and stained by acid fast stain (AFS) for the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…Kaewthamasorn and Wongsamee (2006) screened 207 faecal samples of beef cattle in Nan Province, Northern Thailand but did not detect either parasite in their samples. While we did not detect either Cryptosporidium or Giardia in faecal samples of dairy cattle at our study site, other Thai studies have (Inpankaew et al, 2010;Jittapalapong et al, 2006Jittapalapong et al, , 2011Nuchjangreed et al, 2008). In Northern Thailand, the seroprevalence of Cryptosporidium parvum infection of 642 dairy cows were 3.3%, 5.1% and 3.0% in the provinces of Chiang Mai, Chiang Rai and Lampang, respectively (Inpankaew et al, 2009).…”
Section: Livestock Managementmentioning
confidence: 47%
“…Kaewthamasorn and Wongsamee (2006) screened 207 faecal samples of beef cattle in Nan Province, Northern Thailand but did not detect either parasite in their samples. While we did not detect either Cryptosporidium or Giardia in faecal samples of dairy cattle at our study site, other Thai studies have (Inpankaew et al, 2010;Jittapalapong et al, 2006Jittapalapong et al, , 2011Nuchjangreed et al, 2008). In Northern Thailand, the seroprevalence of Cryptosporidium parvum infection of 642 dairy cows were 3.3%, 5.1% and 3.0% in the provinces of Chiang Mai, Chiang Rai and Lampang, respectively (Inpankaew et al, 2009).…”
Section: Livestock Managementmentioning
confidence: 47%
“…in HIVinfected patients, in cattle, and in food (green mussels) have been already reported from Thailand (Uga et al 2000;Gatei et al 2002;Saksirisampant et al 2002;Tiangtip and Jongwutiwes 2002;Nuchjangreed et al 2008;Srisuphanunt et al 2009), no outbreaks of waterborne cryptosporidiosis or giardiasis have been reported in the country, and they could not be included in the systematic review covering all reports worldwide of waterborne protozoan outbreaks by Karanis et al (2007). No data exist regarding protozoan parasite concentrations in wastewaters or in reuse and recycling of wastewaters for agriculture and industry and in backwash water from drinking water treatment plants in Thailand.…”
Section: Dicussionmentioning
confidence: 78%
“…Since then, there have been numerous reports of cryptosporidiosis in different countries and regions [5,6,17,19,20,27]. However, only a few publications have documented Cryptosporidium prevalence among animals in China [7,40].…”
Section: Discussionmentioning
confidence: 99%